Norway spruce (Picea abies) laccases: Characterization of a laccase in a lignin‐forming tissue culture. Issue 4 (April 2015) - Koutaniemi, Sanna; Malmberg, Heli A.; Simola, Liisa K.; Teeri, Teemu H.; Kärkönen, Anna
Abstract Secondarily thickened cell walls of water‐conducting vessels and tracheids and support‐giving sclerenchyma cells contain lignin that makes the cell walls water impermeable and strong. To what extent laccases and peroxidases contribute to lignin biosynthesis in muro is under active evaluation. We performed an in silico study of Norway spruce (Picea abies (L.) Karst.) laccases utilizing available genomic data. As many as 292 laccase encoding sequences (genes, gene fragments, and pseudogenes) were detected in the spruce genome. Out of the 112 genes annotated as laccases, 79 are expressed at some level. We isolated five full‐length laccase cDNAs from developing xylem and an extracellular lignin‐forming cell culture of spruce. In addition, we purified and biochemically characterized one culture medium laccase from the lignin‐forming cell culture. This laccase has an acidic pH optimum (pH 3.8–4.2) for coniferyl alcohol oxidation. It has a high affinity to coniferyl alcohol with an apparent Km value of 3.5 μM; however, the laccase has a lower catalytic efficiency (Vmax/Km) for coniferyl alcohol oxidation compared with some purified culture medium peroxidases. The properties are discussed in the context of the information already known about laccases/coniferyl alcohol oxidases of coniferous plants.